Hacia un paradigma de la sostenibilidad para la bioética de V. R. Potter: entre el desarrollo sostenible, el ecodesarrollo y la racionalidad ambiental (2021)
The article asserts a foundational relationship between the Potterian bioethical vision and the role of sustainability. Considering that V.R. Potter did not develop conceptually how and from what approach the sustainability of humanity should be understood, it becomes necessary to show such conceptual development. Thus, Potter’s bioethical vision could be rethought and updated to face the challenge of humanity nowadays. In this order of ideas, it is proposed to analyze descriptively the theoretical approaches and the conceptual extensions of the concept of sustainability to recognize in what sense they contribute in the construction of an acceptable survival for humanity, in terms of global bioethics. To this end, the theoretical theme of sustainable development is presented, highlighting its systemic and intergenerational component, while criticizing its economic growth structure and its incompatibility with the Potterian bioethical vision. Afterwards, the alternative proposal of eco-development and environmental rationality is presented, as important elements to broaden the sustainability paradigm. Finally, it concludes with an integration of elements of both theoretical themes as a starting point for thinking about sustainability from a bioethical perspective.